2016
DOI: 10.1111/jcpp.12651
|View full text |Cite
|
Sign up to set email alerts
|

Research Review: Neural response to threat in children, adolescents, and adults after child maltreatment – a quantitative meta‐analysis

Abstract: The meta-analysis confirms that maltreatment is related to increased bilateral amygdala reactivity and also shows that maltreatment affects multiple additional structures in the brain that have received little attention in the literature. Thus, although the majority of studies examining maltreatment and brain function have focused on the amygdala, these findings indicate that the neural consequences of child maltreatment involve a broader network of structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
159
2
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(180 citation statements)
references
References 57 publications
(60 reference statements)
14
159
2
5
Order By: Relevance
“…In functional MRI studies, we and others have shown that childhood trauma and adversity are associated with increased amygdala reactivity particularly to negative stimuli (e.g. [3847]) as well as decreased resting functional coupling between the amygdala and vmPFC [48,49]. It is worth noting that such changes have been observed across healthy and psychiatric samples of youth.…”
Section: Impacts Of Child Trauma Exposure On Neurodevelopmentmentioning
confidence: 73%
See 1 more Smart Citation
“…In functional MRI studies, we and others have shown that childhood trauma and adversity are associated with increased amygdala reactivity particularly to negative stimuli (e.g. [3847]) as well as decreased resting functional coupling between the amygdala and vmPFC [48,49]. It is worth noting that such changes have been observed across healthy and psychiatric samples of youth.…”
Section: Impacts Of Child Trauma Exposure On Neurodevelopmentmentioning
confidence: 73%
“…In these studies, amygdala hyperactivation has been reported in only one study of pediatric PTSD [38], with no difference (negative studies) in three others [5557]. Similar to the case for hippocampal volume, the general lack of average amygdala activation differences is curious given relatively consistent reports of amygdala hyperactivation in both adult PTSD [68] and adolescents/adults with a history of childhood trauma [47]. As in the case of hippocampal volume, this could represent a delayed developmental effect, whereby amygdala hyperactivation is not fully apparent until adulthood.…”
Section: Functional Brain Abnormalities During Emotion Processing In mentioning
confidence: 97%
“…Adults with childhood maltreatment exhibited increased STG activity during emotional processing (Hein and Monk, 2016). A meta-analysis associated an inter-connected network of brain regions including the STG during experiences of guilt (Gifuni et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…negative facial expressions) (Dannlowski et al, 2012(Dannlowski et al, , 2013Hein & Monk, 2017;Maheu et al, 2010;E. McCrory, De Brito, & Viding, 2011;E.…”
Section: Brain Functioningmentioning
confidence: 99%